Transforming school personnel management with artificial intelligence: Evidence from elementary school leadership practices - Ahmad Gawdy Prananosa; M. Rusni Eka Putra; Marianita; Lendri Alpikar (Journal of Educational Management and Instruction (JEMIN), 2026)
The increasing integration of artificial intelligence (AI) in educational environments has transformed instructional and administrative practices; however, empirical studies examining AI-based management of teaching and educational personnel in elementary schools remain limited. This study aims to investigate how AI can support the management of teaching and educational staff in elementary schools, focusing on five key managerial dimensions: planning, recruitment and selection, performance assessment, competency development, and ethical use of AI. The research employed a sequential exploratory mixed-methods design, involving a quantitative survey of 60 teachers and school principals in elementary schools in Silampari District, Lubuk Linggau City, Indonesia, followed by semi-structured interviews with 10 participants to obtain deeper insights into the implementation of AI-based management practices. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic analysis. The findings indicate that educators generally express strong support for AI integration in school management, particularly in improving personnel planning, enhancing recruitment efficiency, supporting data-driven performance evaluation, facilitating professional competency development, and ensuring ethical governance and data security. Qualitative findings further reveal that AI-supported digital platforms are increasingly used to streamline administrative coordination and support evidence-based decision-making in school management. These findings highlight the strategic role of AI in strengthening educational personnel management while emphasizing the need for institutional readiness, ethical governance, and professional capacity development for sustainable AI integration in elementary school management.